Comparative Analysis of GTAW, GMAW, and FCAW Welding Results on A36 Steel Against Tensile Test and Macrostructure - Herman Pratikno; Hafizh Abiyyuda; Wimala Lalitya Dhanista (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2022)
Offshore building construction is inseparable from the fabrication process. Fabrication process that has an important role in terms of engineering, material repair and welding process. In offshore building construction, a precise welding method is needed on A36, where A36 steel is one of the main materials in the fabrication process of offshore buildings. In this study a comparison of welding results of GTAW, GMAW, and FCAW on A36 steel against Tensile Test and Macrostructure Test. The results of this research show that the best tensile test results are the GTAW welding method with an average value of ultimate strength of 462,168 MPa. Macrostructure testing which has the widest HAZ width is the GTAW welding method of 18,71 mm.